Strategi Manajemen Operasional dalam Meningkatkan Efisiensi Lembaga Kursus Komputer Karya Prima - Sani Susanti; Anugerah Setiawan; Adinda Syafira; Arum Dwi Saputri; Carissa Mumtaza; Dimas Istiqo; Mutiara Mutiara (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to identify the problems faced by the Karya Prima Computer course study group. The research method used is a qualitative descriptive approach by collecting data through interviews and observations of residents studying the Karya Prima computer course. The research results show several main problems, namely related to the marketing of Karya Prima computer courses, where information regarding these computer courses is still difficult to reach in the community. As a solution, the group offers a medium, namely, where the group will create a browser/poster to market the Karya Prima computer course so that it can be reached by the local community.